Proximate Composition of Clarias gariepinus Fed Graded Levels of Sesame indicum (Beni seed) Diets (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This present study investigates the effect of replacing fishmeal with varying levels of Beni seed (Sesamum indicum) meal on the diet of Clarias gariepinus. Three hundred and sixty (360) healthy C. gariepinus (African mud catfish) were stocked in eighteen (18) experimental tanks and fed different graded levels of diets that were developed to contain 40% crude protein using graded levels of sesame seed meal (0%, 25%, 50%, 75%, and 100%) as a replacement of fish meal. Proximate compositions of both diets and fish carcasses were analyzed following the AOAC (2019) methods. Significant differences (p
Keywords: Beni seed meal; Sesamum indicum; Fishmeal replacement; Clarias gariepinus nutrition; Aquaculture feed formulation